FLUCTUATIONS OF LITHUANIAN ECONOMY: IDENTIFICATION RULES AND FEATURES - Valkauskas, R. (Ekonomika, 2012)
This article is focussed on the problem of economic-statistical calculations and includes an economic-statistical research of economic fluctuations. The author also discusses the rules for statistical identification of economic welfare, economic development features of Lithuania after it became a member of the European Union. The notion of specific economic indicators, their classification issues, and the role and place of economic indicators presenting a systemic view of the country’s economy through identification of economic activities and their development are also discussed.The article deals also with the methodologies based on various statistical methods and offers a methodology for revealing the components of economic fluctuations. A common notion is that the methodologies using analytical time series smoothed with the least squares method for revealing economic fluctuation components are best. The author proposes a methodology for calculating and evaluating the components of economic fluctuations, based on gross domestic product data.